A Novel Electrochemical Method for the Sensitive Determination of Aflatoxin B1 Using a Bivalent Binding Aptamer‐cDNA Structure. Issue 3 (3rd August 2022) - Sameiyan, Elham; Lavaee, Parirokh; Ramezani, Mohammad; Alibolandi, Mona; Khoshbin, Zahra; Abnous, Khalil; Taghdisi, Seyed Mohammad
Abstract: In this study, a simple electrochemical sensing platform with the employment of a bivalent binding aptamer‐cDNA probe (BBA‐cDNA) structure is constructed for the detection of aflatoxin B1 (AFB1 ) as a mycotoxin. The BBA‐cDNA structure is composed of two strands of aptamer (Apts) and their complementary strand (CS). Using a simple but accurate design, the presented measurement approach showed enhanced sensitivity and selectivity for AFB1 detection with a LOD of 0.1 ng/mL. The approach presented in this study can be applied to the development of biosensors for the measurement of various toxins by substituting the proper aptamers and complementary strands. Abstract :